2022
DOI: 10.3389/fcell.2022.859236
|View full text |Cite
|
Sign up to set email alerts
|

Computational Metabolomics Reveals the Potential Mechanism of Matrine Mediated Metabolic Network Against Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a complex issue in cancer treatment in the world at present. Matrine is the main active ingredient isolated from Sophora flavescens air and possesses excellent antitumor effects in HCC. However, the specific underlying mechanisms, especially the possible relationships between the anti-HCC effect of matrine and the related metabolic network of HCC, are not yet clear and need further clarification. In this study, an integrative metabolomic-based bioinformatics algorithm was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Based on these findings, we hypothesize that matrine not only alters LDLR expression levels through transcriptional regulation but also modulates lipid metabolism by affecting metabolic pathway proteins. In addition, since matrine primarily influences lipid metabolism and other metabolic pathways, metabolomics research will undoubtedly enhance our understanding of matrine’s metabolic regulation in future studies, , which will provide a more comprehensive insight into the molecular pathways modulated by matrine.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, we hypothesize that matrine not only alters LDLR expression levels through transcriptional regulation but also modulates lipid metabolism by affecting metabolic pathway proteins. In addition, since matrine primarily influences lipid metabolism and other metabolic pathways, metabolomics research will undoubtedly enhance our understanding of matrine’s metabolic regulation in future studies, , which will provide a more comprehensive insight into the molecular pathways modulated by matrine.…”
Section: Discussionmentioning
confidence: 99%
“…Creatine is among the power sources utilized by tumor cells during growth (Kazak & Cohen, 2020), and choline can enhance fatty acid usage to avoid the aberrant accumulation of liver fat. Furthermore, matrine can effectively boost intracellular choline levels and ameliorate lipid metabolism issues in HCC (Wang et al, 2022).…”
Section: Liver Cancermentioning
confidence: 99%
“…There have been a larger number of studies exhibiting that Matrine has multiple pharmacological properties, containing anti‐tumor, anti‐inflammatory, anti‐viral, and analgesic (Lin et al., 2022). In fact, it has been reported that Matrine might repress HCC progression by regulating different targets or pathways (Lin et al., 2020; Wang et al., 2022). Yet, the specific molecular mechanism of Matrine on anti‐tumor role in HCC is still poorly defined.…”
Section: Introductionmentioning
confidence: 99%